Studio Perancangan Arsitektur Kota: Kampung Wisata Hijau Organik Cilegong, Desa Mekarwangi - Muhammar Khamdevi; Danang Harito Wibowo (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2018)
The formal housing expansion by private property developers in Tangerang District has the potential to generate "urban void" due to the degradation of the quality of local informal settlements into slums. Between the rich and the poor do not have shared space, to meet and to communicate, but instead hindered by the construction of a concrete wall separating the two sides with a lame gap. Mekarwangi Village is one of the villages in Kecamatan Cisauk, Tangerang Regency, which some part of the area will be built formal housing. To overcome the negative impact, it is necessary step in integrating it with formal housing. One of them is to plan a comperhensive settlement design, but also affordable and in accordance with the local character, and promote sustainability. Community service activities are integrated along side with research into the teaching; the course Urban Design Studio. Beside lecturers and students, this activity also involved the local residents and local agencies. The scope of this case study is in one neigborhoods of Mekarwangi Village; Kampung Cilegong. How the settlement planning and design will be suitable for Kampung Cilegong? This research uses qualitative method to get deeper problem. This study aims to find a solution for Mekarwangi Village in the future. This activity is succeeded and satisfied the citizens of Kampung Cilegong, Mekarwangi Village